1982
DOI: 10.1084/jem.155.3.809
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of bacterial resistance to complement-mediated killing. II. C8 and C9 release C5b67 from the surface of salmonella minnesota S218 because the terminal complex does not insert into the bacterial outer membrane

Abstract: The mechanism for consumption of terminal complement components and release of bound components from the surface of serum-resistant salmonella minnesota S218 was studied. Consumption of C8 and C9 by S218 occurred through interaction with C5b67 on the bacterial surface because C8 and C9 were consumed when added to S218 organisms previously incubated in C8-deficient serum and washed to remove all C5b67 on the bacterial surface because C8 and C9 were consumed when added to S218 organisms previously incubated in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(87 citation statements)
references
References 16 publications
5
81
1
Order By: Relevance
“…48 and 49). Comparing Salmonella minnesota with smooth (long LPS chains) and rough phenotype (short LPS chains), C3 binding and C5b-9 consumption after Ab binding were similar or increased with the smooth phenotypes but this was associated with "failure of complexes to bind hydrophobically in the outer membrane" of these smooth variants (50). Similar findings have been described for Salmonella montevideo (51) and Pseudomonas aeruginosa where serum resistance is associated with long LPS chains.…”
Section: Discussionsupporting
confidence: 73%
“…48 and 49). Comparing Salmonella minnesota with smooth (long LPS chains) and rough phenotype (short LPS chains), C3 binding and C5b-9 consumption after Ab binding were similar or increased with the smooth phenotypes but this was associated with "failure of complexes to bind hydrophobically in the outer membrane" of these smooth variants (50). Similar findings have been described for Salmonella montevideo (51) and Pseudomonas aeruginosa where serum resistance is associated with long LPS chains.…”
Section: Discussionsupporting
confidence: 73%
“…3, 4 2, and 3). Therefore, we postulate, based pn this and previous work (12,13,14) that a critical density (>20%) of long O-Ag side chains is required to protect the cells from serum killing and that the O-Ag protection is a result of steric hindrance of C5b-9 access to hydrophobic domains of the outer membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Complement activation by smooth, enteric gram-negative bacteria is efficient, and the bactericidal C5b-9 complex is formed on the surface of such smooth cells (13). However, in contrast to the stable, hydrophobic interaction of C5b-9 with rough cells, the C5b-9 complex is bound by weak hydrophilic interactions to smooth cells and is released from the surface (14). Consequently, it is not bactericidal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of serum-resistant Salmonella minnesota have suggested that resistance in this bacterium is related to failure of the complement membrane attack complex (MAC) to insert into hydrophobic domains of the outer membrane (17,18). We undertook the following studies to assess the interaction of the complement system with resistant and sensitive _IV.. gonorrhoeae to characterize the relationship of the complement system to serum resistance.…”
mentioning
confidence: 99%